PENINGKATAN HASIL BELAJAR IPA DENGAN PEMBELAJARAN TEKNIK TARI BAMBU PADA SISWA KELAS IV SD - Limbong, Lasmauli (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2014)
This classroom action research aims to improve the students learning result in electrolyte and nonelectrolyte solutionthrough cooperative model of Bambu dance. There were30 students Kelas IV SDN Duri Utara 01 Pagi Kecamatan Tambora Jakarta Barat participated this classroom action research, wich is conducted collaboratively with teachers during two cycles of learning.Each cycle consists of three phases namely planning action, action, observation and reflection. Data at each cycle the test result of learning, observation, and interviews. Action analysis results show the percentage of students in the classroom increases learning and achieve success indicator. Obtained total percentage of student learning outcomes in the first cycle that reached 48.14% (by 13 students) with poor category, while the second cycle of the total percentage of students achieving learning is 78.57% (by 22 students) with the category of very good. The result is expected teachers can use bamboo dance model as an alternative method in teaching.